Clinical Outcomes in Non Valvular Atrial Fibrillation Patients Receiving Oral Anticoagulation Therapy using CHA2DS2-VASc and HAS-BLED Scores: A Cohort Study from Western Gujarat, India - Sohilkhan Riyazkhan Pathan; Bharat M Gajjar; Sunilkumar Karna; Kushal Pujara (Journal of Clinical and Diagnostic Research)
Introduction: Non Valvular Atrial Fibrillation (NVAF) is one of the most common sustained arrhythmias. The Congestive heart failure, Hypertension, Age, Diabetes, Stroke/TIA (or Thrombembolism), Vascular disease, Age, Sex category (for CHA2DS2-VASc) score, which includes Congestive heart failure, Hypertension, Age ≥75 (doubled), Diabetes, Stroke (doubled), Vascular disease, Age 65-74 and Sex category (female), as well as the Hypertension, Abnormal Renal/Liver function, Stroke, Bleeding history or predisposition, Labile International Normalised Ratio (INR), Elderly, Drugs/alcohol concomitantly (for HAS-BLED)-comprising Hypertension, Abnormal renal/liver function, Stroke, Bleeding history or predisposition, Labile INR, Elderly and Drugs/alcohol concomitantly-assists in assessing bleeding risk. However, the outcomes of NVAF have remained underreported in Gujarat, western India. Aim: To characterise thromboembolic and bleeding risks using the CHA2DS2-VASc and HAS-BLED scores among NVAF patients receiving oral anticoagulation therapy. Materials and Methods: This ambidirectional cohort study (retrospective and prospective) was conducted over an 11-year period (January 2014 - December 2024) at the Bhanubhai and Madhuben Patel Cardiac Centre, Shree Krishna Hospital and Medical Research Centre, Karamsad, Gujarat, India, a tertiary care hospital in a rural setting. The study evaluated NVAF cases based on age, sex, co-morbidities, anticoagulation therapy {Vitamin K Antagonists (VKA) or Novel Oral Anticoagulants (NOAC)} and clinical outcomes, including stroke and bleeding events. HAS-BLED scores, treatment strategies and clinical outcomes were compared across CHA2DS2-VASc risk groups (low ≤3, intermediate 4-5 and high ≥6). Statistical analysis was performed using statistical software Statistical Analysis System (SAS) Viya (SAS Institute Inc., NC, USA). Comparisons of risk groups used the Mann-Whitney U test, Chi-square/Fisher’s-exact test and Kruskal-Wallis test as appropriate. The Cochrane-Armitage trend test evaluated anticoagulant use patterns. A p-value <0.05 was considered statistically significant. Results: Among 347 NVAF patients, CHA2DS2-VASc scores were significantly higher in females (p<0.0001), indicating greater thromboembolic risk. Hypertension, diabetes mellitus, ischaemic heart disease, prior stroke, chronic kidney disease and heart failure were strongly associated with risk groups (p<0.0001). High-risk patients were older (median 80 vs. 61 years, p<0.0001) and had higher HAS-BLED scores (p<0.0001). NOACs were more frequently prescribed to high-risk patients than VKAs (p<0.0001), with combination antithrombotic therapy being more common among NOAC users (p=0.001). Major bleeding events, including ischaemic and haemorrhagic strokes, were significantly more frequent in high-risk patients (p<0.0001), while mortality was highest in the intermediate-risk group (25.0%, p<0.0001). Conclusion: The present study observed sex-based differences in CHA2DS2-VASc scores and their association with thromboembolic risk. Higher scores were associated with advanced age, multiple co-morbidities, increased bleeding risk and the use of NOACs. Adverse clinical outcomes, including major bleeding, were more frequent in higher-risk groups, indicating the need for personalised anticoagulation therapy based on the patient’s bleeding and thromboembolic risk.